Developmental changes in the relationship between magnitude acuities and mathematical achievement in elementary school children. Issue 7 (9th August 2017) - Park, Yunji; Cho, Soohyun
Abstract: The present study examined the developmental change in number and length acuities and their respective relationship with achievement in various domains of mathematics in second vs. fourth graders. Length acuity was measured with a comparison task, in which participants were asked to choose the longer between a pair of lines. Number acuity was measured with a comparison task, in which the participants were asked to choose the more numerous between a pair of dot arrays. Within each grade, length acuity was more precise compared to number acuity. Number acuity was higher in fourth compared to second grade, but length acuity did not differ between grades manifesting a ceiling effect. In second grade, only length acuity was correlated with overall math achievement, especially Geometry and Arithmetic. In fourth grade, only number acuity was correlated with overall mathematical achievement, especially Number Concept and Applied Problems. Taken together, the present study demonstrates that the relationship between magnitude acuities and math achievement dynamically change over the course of elementary school years and that the strength of this relationship may depend on the type of magnitude and the domain of mathematics.